Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

This is given in my module as a part of a problem's solution:

$$m^4 + 4 = 0 $$ $$\Rightarrow m = 1 \pm i,-1\pm i$$

I am not getting how this conversion is taking place,could somebody explain?

share|improve this question
1  
It follows from Euler's formula. –  Qiaochu Yuan Feb 20 '11 at 12:59
1  
Well, a polynomial of degree $4$ over the complex numbers has at most 4 roots; these four numbers are roots, so they are *all the roots... –  Arturo Magidin Feb 20 '11 at 23:30
add comment

4 Answers

up vote 7 down vote accepted

One way to look at it is like this: $$ m^4+4=0\implies m^4=-4\implies m^2=\pm 2i. $$ But $$ m^2=2i\implies m=\pm\sqrt{2}\sqrt{i}. $$ Also, $$ m^2=-2i\implies m=\pm i\sqrt{2}\sqrt{i}. $$ Now you can use that fact that there are two square roots of $i$, $$ \frac{1+i}{\sqrt{2}}\ \text{and}\ \frac{1+i}{-\sqrt{2}} $$ to simplify each possibility, and get the $4$ values of $m$ you mentioned.

share|improve this answer
add comment

You can also factor $x^4+4=(x^2-2x+2)(x^2+2x+2)$.

share|improve this answer
1  
BTW, this also proves that $n^4+4$ is never a prime, for $n$ an integer. See math.stackexchange.com/questions/21146/… –  lhf Feb 20 '11 at 15:31
add comment

Here $m = (-4)^{1/4}$.

Now $-4 = 4(\cos(\theta) + i\sin(\theta))$ in polar form where $\theta = (2n-1)\pi$.

By de Moivre's theorem

$m = (-4)^{1/4} = 4^{1/4}(\cos(\frac{\theta}{4}) + i\sin(\frac{\theta}{4}))$

For $n = 0$, $\displaystyle m = \sqrt{2}\left(\frac{1}{\sqrt{2}} - \frac{i}{\sqrt{2}}\right) = 1 - i$,

For $n = 1$, $\displaystyle m = \sqrt{2}\left(\frac{1}{\sqrt{2}} + \frac{i}{\sqrt{2}}\right) = 1 + i$,

For $n = 2$, $\displaystyle m = \sqrt{2}\left(-\frac{1}{\sqrt{2}} + \frac{i}{\sqrt{2}}\right) = -1 + i$,

For $n = 3$, $\displaystyle m = \sqrt{2}\left(-\frac{1}{\sqrt{2}} - \frac{i}{\sqrt{2}}\right) = -1 - i$

share|improve this answer
add comment

HINT $\rm\ -4 = m^4\ \Rightarrow\ \pm 2\ i = m^2 = (a+b\ i)^2 = a^2-b^2 + 2\:a\:b\ i\ \Rightarrow\ |a| = |b| = 1\:$.

share|improve this answer
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.